Detection of small molecule concentration gradients in ocular tissues and humours. (25th November 2019) - Boughton, Berin A.; Thomas, Oliver R.B.; Demarais, Nicholas J.; Trede, Dennis; Swearer, Stephen E.; Grey, Angus C.
Abstract: The eye is an elegant organ consisting of a number of tissues and fluids with specialised functions that together allow it to effectively transmit and transduce light input to the brain for visual perception. One key determinant of this integrated function is the spatial relationship of ocular tissues. Biomolecular distributions within the main ocular tissues cornea, lens, and retina have been studied extensively in isolation, yet the potential for metabolic communication between ocular tissues via the ocular humours has been difficult to visualise. To address this limitation, the current study presents a method to map spatial distributions of metabolites and small molecules in whole eyes, including ocular humours. Using a tape‐transfer system and freeze‐drying, the spatial distribution of ocular small molecules was investigated in mouse, rat, fish (black bream), and rabbit eyes using negative ion mode MALDI imaging mass spectrometry. Full‐scan imaging was used for discovery experiments, while MS/MS imaging for identification and localisation was also demonstrated. In all eyes, metabolites such as glutathione and phospholipids were localised in the main ocular tissues. In addition, in rodent eyes, major metabolites were distributed relatively uniformly in ocular humours. In contrast, both uniform and spatially defined ocular metabolite distributions were observed in the black bream eye. Tissue and ocular humour distributions were reproducible, as demonstrated by the three‐dimensional analysis of a mouse eye, and able to be captured with high spatial resolution analysis. The presented method could be used to further investigate the role of inter‐tissue metabolism in ocular health, and to support the development of therapeutics to treat major ocular diseases.